"Snowing" Graphene using Microwave Ovens. Issue 40 (21st August 2018) - Sun, Yangyong; Yang, Liangwei; Xia, Kailun; Liu, Haizhou; Han, Dong; Zhang, Yingying; Zhang, Jin
Abstract: Developing a simple and industrially scalable method to produce graphene with high quality and low cost will determine graphene's future. The two conventional approaches, chemical vapor deposition and liquid‐phase exfoliation, require either costly substrates with limited production rate or complicated post treatment with limited quality, astricting their development. Herein, an extremely simple process is presented for synthesizing high quality graphene at low‐cost in the gas phase, similar to "snowing, " which is catalyst‐free, substrate‐free, and scalable. This is achieved by utilizing corona discharge of SiO2 /Si in an ordinary household microwave oven at ambient pressure. High quality graphene flakes can "snow" on any substrate, with thin‐flakes even down to the monolayer. In particular, a high yield of ≈6.28% or a rate of up to ≈0.11 g h −1 can be achieved in a conventional microwave oven. It is demonstrated that the snowing process produces foam‐like, fluffy, 3D macroscopic architectures, which are further used in strain sensors for achieving high sensitivity (average gauge factor ≈ 171.06) and large workable strain range (0%–110%) simultaneously. It is foreseen that this facile and scalable strategy can be extended for "snowing" other functional 2D materials, benefiting their low‐cost production and wide applications. Abstract : Scalable preparation of "snowing" graphene flakes with high quality and low‐cost by a facile, substrate‐free and catalyst‐free process is demonstrated. A high yield and rate of graphene flakes can be achieved. It is demonstrated that the fluffy macroscopic architectures by snowing graphene can be used in high‐performance strain sensors for achieving high sensitivity and large workable strain range.